2004
DOI: 10.1002/chin.200406220
|View full text |Cite
|
Sign up to set email alerts
|

Monoarylhydrazones of α‐Lapachone: Synthesis, Chemical Properties and Antineoplastic Activity.

Abstract: Monoarylhydrazones of α-Lapachone: Synthesis, Chemical Properties and Antineoplastic Activity. -(RENOU*, S. G.; ASIS, S. E.; ABASOLO, M. I.; BEKERMAN, D. G.; BRUNO, A. M.; Pharmazie 58 (2003) 10, 690-695; Dep. Quim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…Although β-lapachone can bind to DNA in vitro, its affinity for DNA does not seem to correlate to its antineoplasic activity. 31 On the other hand, enzymes involved in DNA metabolism have been reported to be inhibited in vitro by β-lapachone. 20 DNA topoisomerases were good candidate targets to be tested because: 1) β-lapachone inhibits topoisomerases I and IIα in vitro, 22,30 and 2) β-lapachone induces topoisomerase II mediated DNA damage in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although β-lapachone can bind to DNA in vitro, its affinity for DNA does not seem to correlate to its antineoplasic activity. 31 On the other hand, enzymes involved in DNA metabolism have been reported to be inhibited in vitro by β-lapachone. 20 DNA topoisomerases were good candidate targets to be tested because: 1) β-lapachone inhibits topoisomerases I and IIα in vitro, 22,30 and 2) β-lapachone induces topoisomerase II mediated DNA damage in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…13 O lapachol (1) e seus derivados, como, por exemplo, a α-xiloidona (deidro-α-lapachona) (2) e a deidro-iso-α-lapachona (3), são naftoquinonas naturais isoladas das cascas das árvores da família Bignoneacea, como a Tabebuia spp., [1][2][3] Haplophragma adenophylum, 14 Oroxylum indicum (L.) Vent, 15 Newbouldia laevis Seem., 16 Radermachera sinica Hemsl 17 e mais recentemente da Catalpa ovata; 18 enquanto a rinacantina-A (4) foi isolada em 1988 da Rhinacanthus nasutus (L.) Kurz (Acanthaceae). 19 Lapachol (1), α-xiloidona (2) e a deidro-iso-α-lapachona (3) possuem atividades biológicas comuns a esta classe de substâncias, como as descritas acima, [1][2][3][4][5][6][7][8][9][10][11][12][13]18,[20][21][22]23 e a rinacantina-A (4) não apresentou citotoxicidade 19 (Figura 1). Devido às atividades biológicas dos derivados cíclicos do lapachol (1), muitos grupos de pesquisa vêm estudando suas preparações.…”
Section: Introductionunclassified
“…This study only found aberrant crypt foci of hyperplastic and dysplastic types; the first type was found in all animals with histopathological changes, and the second was uncommon in all groups. Most of the work makes only descriptive evaluation of histopathology slides stained by using hematoxylin and eosin, and present evaluation results with immunohistochemistry, genetics (DNA) or biochemicals 1,10,11,13,15,16,22 . Only one animal in group V showed no pathological changes, which brought no significant changes in reducing aberrant crypt foci in mice that were induced with azoxymethane colon tumor and treated with β-lapachone.…”
Section: Groupsmentioning
confidence: 99%